Effects of Combined Magnetic Fields Treatment and Nano-Hydroxyapatite Coating on Porous Biphasic Calcium Phosphate Bone Graft in Rabbit Spinal Fusion Model. Issue 11 (1st June 2018) - Zhuo, Xianglong; Li, Chentian; Li, Bing; Li, Zhaoyang; Lv, Hongbin; Huang, Jianjun; Xu, Daqi; Hu, Jianzhong
Abstract : Study Design: An animal experimental study was designed to investigate the efficacy of combined magnetic fields (CMF) treatment and nano-hydroxyapatite (HA) coating in the biphasic calcium phosphate (BCP) graft in posterolateral lumbar fusion. Objective: To evaluate the effects of CMF treatment and nano-HA/BCP and their combination effect in posterolateral lumbar fusion. Summary of Background Data: Enhancement of artificial bone graft bioeffects could improve spinal fusion outcomes. The bone graft integration is vital in spinal fusion, nano-HA coating, and CMF treatment were reported as effective methods to improve bone graft integration. Methods: A bilateral transverse process fusion model was performed on 32 rabbits. The CMF treatment was performed for 30 minutes per day postoperation. The fusion rate, new bone formation, artificial bone graft-autologous bone fusion interface in x-ray and scanning electron microscopy, biomechanics property of fusion rate, histological fusion condition, artificial bone residual rate, and immunohistochemistry assessment of bone morphogenetic protein 2 (BMP-2) and Transforming growth factor beta 1 (TGF-β1) expression were observed at 9th week after surgery. Results: CMF treatment and nano-HA coating increased the fusion rate, adjusted optical density index, intensity of binding of artificial and autologous bone, bone growth rate, and bending stiffness. CMF treatment also significantly increased BMP-2 and TGF-β1 expression in fusion region while nano-HA coating significantly decreased artificial bone residual rate. Conclusion: Our findings suggest that porous nano-HA/BCP graft could significantly improve spine fusion outcome with excellent bioactivity, biocompatibility and degradability and CMF treatment could significantly improve spine fusion outcome by improving bioactivity and biocompatibility of artificial bone graft in rabbit. Combination of CMF treatment with nano-HA/BCP graft could significantly increase posterolateral lumbar fusion rate in rabbit, which would be a potential strategy for spine fusion preclinical study. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text